Rural Face, Urban Mask: Architecture of Communal Form and Collective Practice in Two Chinese Villages from 2010 to 2015. Issue 1 (2nd January 2017) - Ren, Xiang
Abstract: "Rural reconstruction" has become an important and much-discussed theme within Chinese architectural practice and academia in recent years. The approach adopted by architects and intellectuals in this field tends to be oriented towards humanitarian service and cultural production. In this study I argue that not enough attention is being given to the kinds of social production and communal form that are typically constructed through collective building and economic practices in Chinese villages. This paper compares the approaches to village revitalization taken by two recent architectural projects in two Chinese villages, both attempt to give fresh meaning to the old word "commune." By examining the extent to which input from creative outsiders can reconfirm or reinvent the value and potential of "commune" in their efforts to effect socio-cultural transformation in Chinese villages, my conclusion is that architecture in Chinese villages needs to work with more communal forms of collective practice in order to achieve a more socially resilient rural reconstruction.